Extended thermodynamic analysis of a charged Horndeski black hole - Yun Soo Myung (Physics Letters B)
We perform the thermodynamic analysis of a charged Horndeski black hole (CHB) with mass m and charge q obtained from the Einstein-Horndeski-Maxwell theory. There are two solution branches: one is for the CHB and the other is for the naked singularity (NS). Thermodynamic behavior for the CHB is similar to that for the Reissner-Nordström black hole but its Helmholtz free energy is always positive. If the NS point is included as an extremal point, then the Helmholtz free energy is always negative, implying that the globally stable region is achieved anywhere. For the NS, its temperature has a maximum point, its heat capacity remains negative without having Davies point, and its free energy decreases without limitation as the charge q increases.